Relative age selection bias does not translate into a playing-time advantage: evidence from Italian Serie A football - Brustio, P. R.; Ungureanu, A. N.; Beratto, L.; Li Volsi, D.; Lupo, C. (Frontiers in Psychology, 2026)
Introduction: The Relative Age Effects (RAEs) represent a bias in talent identification and selection processes, favouring athletes born earlier in the selection year. This study aimed to (i) quantify the prevalence and magnitude of the RAEs in Italian elite football (Serie A), considering age categories, playing positions, and team ranking, and (ii) examine whether RAEs are associated with selection- and participation-related outcomes (i.e., match appearances, total playing time, and consistency of match participation).